Intra‐Crater Eruption Dynamics at Nyiragongo (D.R. Congo), 2002–2021. Issue 4 (20th April 2022) - Barrière, Julien; Nicolas d'Oreye,; Smets, Benoît; Oth, Adrien; Delhaye, Louise; Subira, Josué; Mashagiro, Niche; Derauw, Dominique; Smittarello, Delphine; Syavulisembo, Adalbert Muhindo; Kervyn, François
Abstract: Nyiragongo is one of the rare volcanoes on Earth hosting a lava lake. However, the understanding of its plumbing and lava lake systems remains limited, with, until recently, only sporadic or time‐limited historical observations and measurements. Combining dense accurate lava lake and crater floor level measurements based on 1, 703 satellite radar images and topographic reconstructions using photogrammetry, we obtain the first reliable picture and time evolution of intra‐crater erupted lava volumes between the two last flank eruptions in January 2002 and May 2021. The filling of the crater by lava, initiated in 2002 and continued up to May 2021, is seen as an evidence of a long‐term pressure build up of the magmatic system. This filling occurs through irregular pulsatory episodes of rising lava lake level, some of which overflow and solidify on the surrounding crater floor. Pauses of stable molten lava lake level and sudden numerous level drops also marked the summit's eruptive activity. The joint analysis with seismic records available since 2015 revealed that the largest lava lake drops are synchronous with seismic swarms associated with deep magma intrusions, generally preceded by an increase of extrusion rate within the crater. The appearance of a spatter cone in the summit crater in 2016, most likely superficially branched to the lava lake, was a clear marker of the change in eruption dynamics. This first long‐term time series of Nyiragongo's crater topography between two hazardous flank eruptions might further help to better decipher Nyiragongo's past and future behavior using multi‐parameter observations. Plain Language Summary: Nyiragongo volcano, in D.R. Congo, stands close to a densely populated area (∼1 million inhabitants). Its Hawaiian‐style eruptive activity essentially consists in a long‐lived molten lava lake or lava fountains in the summit crater lasting for weeks to decades, interrupted by effusive flank eruptions. Nyiragongo erupted on its southern flank in January 2002 and May 2021, draining the lava lake system and opening fissures producing rapid lava flows toward the city of Goma and Lake Kivu. Between these two flank eruptions, the continuous summit eruptive activity took the form of a persistent lava lake progressively filling in the summit crater. Here, we derive accurate elevation measurements of Nyiragongo's crater floor and lava lake surface between the two last flank eruptions from radar satellite instruments and 3D photogrammetric reconstruction. The lava lake, of which the level fluctuates, acts as a growing piezometer connected to the magmatic system as its rim rose by ∼300 m in about 19 years due to overflowing. A combined analysis with seismic records provides important indications on the origins of the observed variations and helps to better understand the link between the continuous eruptive activity and the deeper magmatic processes. Key Points: Processing of 1, 703 satellite radar images leads to the first reliable picture of erupted volumes within Nyiragongo's crater since 2002 We provide a multi‐instrumental analysis with topographic reconstructions using photogrammetry and seismic observations at Nyiragongo Our approach helps to decipher the origins of surface (intra‐crater) evidences of magmatic pressure variations in the plumbing system